Heterozygous RFX6 protein truncating variants are associated with MODY with reduced penetrance. Issue 1 (December 2017) - Patel, Kashyap; Kettunen, Jarno; Laakso, Markku; Stančáková, Alena; Laver, Thomas; Colclough, Kevin; Johnson, Matthew; Abramowicz, Marc; Groop, Leif; Miettinen, Päivi; Shepherd, Maggie; Flanagan, Sarah; et al.
Abstract Finding new causes of monogenic diabetes helps understand glycaemic regulation in humans. To find novel genetic causes of maturity-onset diabetes of the young (MODY), we sequenced MODY cases with unknown aetiology and compared variant frequencies to large public databases. From 36 European patients, we identify two probands with novelRFX6 heterozygous nonsense variants.RFX6 protein truncating variants are enriched in the MODY discovery cohort compared to the European control population within ExAC (odds ratio = 131, P  = 1 × 10−4 ). We find similar results in non-Finnish European (n  = 348, odds ratio = 43, P  = 5 × 10−5 ) and Finnish (n  = 80, odds ratio = 22, P  = 1 × 10−6 ) replication cohorts.RFX6 heterozygotes have reduced penetrance of diabetes compared to commonHNF1A andHNF4A -MODY mutations (27, 70 and 55% at 25 years of age, respectively). The hyperglycaemia results from beta-cell dysfunction and is associated with lower fasting and stimulated gastric inhibitory polypeptide (GIP) levels. Our study demonstrates that heterozygousRFX6 protein truncating variants are associated with MODY with reduced penetrance. Maturity-onset diabetes of the young (MODY) is the most common subtype of familial diabetes. Here, Patel et al. use targeted DNA sequencing of MODY patients and large-scale publically available data to show thatRFX6 heterozygous protein truncating variants cause reduced penetrance MODY.